Stakeholder’s pressures on the firm’s environmental strategy in Malaysia / Rohati Shafie and Loke Siew Phaik - Rohati, Shafie; Loke, Siew Phaik (2015)
The triple focus on “the environment”, “quality”, and “profit” has become a new business mindset motivating the firms to achieve and sustain their competitiveness through better environmental strategy. Although firms are motivated to do so, higher operational costs resulting from the extra prevention and clean-up costs (thus lowering the profitability) often inhibit such willingness. This paper seeks to propose a research framework that analyzes the stakeholder‟s pressures on a firm‟s environmental strategy. Four propositions were generated. The firm‟s commitment to go green can significantly improve its environmental performance. The findings from a focus group with six industry panels are included to illustrate the proposed model.